Finite element analysis of frequency- and temperature-dependent hybrid active-passive vibration damping - Trindade, Marcelo A.; Benjeddou, Ayech; Ohayon, Roger (European Journal of Computational Mechanics, 2000)
A new finite element is formulated and used for the analysis of sandwich damped beams with laminate piezoelectric faces. The viscoelastic damping of the core is accounted for using three models, namely Golla-Hughes-McTavish, Anelastic Displacement Fields and Iterative Modal Strain Energy. Since the first two models increase much the system dimension, a modal reduction is proposed. The reduced models are then applied to the analysis of active constrained layer damping treatments of a cantilever beam, using a constrained input optimal control algorithm. Furthermore, the effect of temperature variations on the control performance is studied.